PENGGUNAAN BATANG NAPIER PADA OPERASI PERKALIAN SISWA KELAS II SD GMIT ENDE 4 - Juwita Merdja; Agnes Pendy (Program Studi Pendidikan Matematika, 2021)
The purpose of this study was to improve the learning outcomes of the multiplication count operation using the props of the Napier rods in grade II SD GMIT Ende 4. The type of research used is a classroom action research with research subjects were all students of grade II SD GMIT as many as 30 people with the research object is a Napier stick. This research was conducted in two cycles. The data collected in this study were student learning outcomes obtained through tests in the form of essay questions and documentation. Data were analyzed using qualitative descriptive analysis. The results of the study showed an increase in student learning outcomes in performing multiplication operation using Napier rods in grade II SD GMIT Ende 4. This was seen from the learning outcomes of the cycle I to cycle II with an average value of 55.7 and 77.67. In addition, 19 students who scored below the KKM were 16 students who scored above the KKM.